ChemInform Abstract: A Phosphine‐Catalyzed Regioselective [3 + 2] Cycloaddition of Ethyl 5, 5‐Diarylpenta‐2, 3, 4‐trienoate with Aromatic Aldehydes and α, β‐Unsaturated Carbonyl Compounds. Issue 16 (April 2015) - Wang, Lu‐Feng; Cao, Xiao‐Ping; Shi, Zi‐Fa; An, Peng; Chow, Hak‐Fun
Abstract A series of methylidene substituted 2, 5‐dihydrofurans is prepared via the reaction of ethyl 5, 5‐diphenylpenta‐2, 3, 4‐trienoate (I) with aryl or hetaryl aldehydes.